Determination of heavy metals in water and sediments of Batang Ai Reservoir and Batang Ai Rive - Liew, Siaw Ying (Universiti Malaysia Sarawak (UNIMAS), 2015)
Heavy metals are one of the vital contaminant in the environment. The objective of the study is to determine the distribution and concentration of zinc (Zn), copper (Cu), iron (Fe), nickel (Ni), lead (Pb), selenium (Se), cadmium (Cd), arsenic (As), manganese (Mn), and mercury (Hg) in water and sediments of Batang Ai Reservoir and Batang Ai River. The water and sediment samples were collected from a total of 16 stations from upstream, downstream and reservoir of Batang Ai River. 4 other stations were located at the fish ponds of SALCRA Batang Ai Inland Fisheries Station. Triplicates of the water and sediment samples were collected from each sampling station. The water at the sub-surface (0-15cm) and the surface sediment were collected, preserved and stored at 4°C before being transported to laboratory for further analysis. In the laboratory, the samples were acid digested, filtered and diluted for analysis with atomic absorption spectrometer (AAS) and mercury analyser. The average concentration of heavy metals in the water decreased in the order of Fe > Zn > Mn > Hg. The average concentration of heavy metals in the sediment decreased in the order of Fe > Mn > Cu > Zn > Ni > Pb > Hg. The quality of sediments was determined through the assessment of contamination factor (CF), geoaccumulation index (Igeo) and pollution load index (PLI). The risk of contamination in Batang Ai Reservoir and Batang Ai River is determined as low.